Estudo teórico das propriedades estruturais e espectroscópicas de redes metalorgânicas com aplicações em saúde, segurança pública, energia e meio ambiente - Rodrigues, Nailton Martins (2018)
Hybrid coordination networks such as metal-organic networks, also known as MOF (Metal Organic Framework), have attracted great attention from the scientific community due to their wide diversity and wide range of applications, however, the investigation of applications of these structures still forms a large area of research, with great exploration potential, either through experimental or theoretical chemistry. The present work aims at the use of computational chemistry methods with focus on semiempirical methods for the study of MOFs, so we will initially address results regarding the evaluation of the prediction capacity of solid phase structures of MOFs containing lanthanide as a metallic center. Performed using the semi-empirical methods Sparkle/AM1, Sparkle/PM3, Sparkle/PM6, Sparkle/PM7, Sparkle/RM1 and RM1. The results obtained from the calculation of optimization of the structures suggest that the Sparkle/PM3 and Sparkle/RM1 methods provide more accurate results, with less variability and great agreement with the experimental data, both structural and luminescent. The health application study initially evaluated the structure of the drug doxorubicin and MOF ZnDBC ([Zn(BDC)(H2O)2]n), and then evaluated the drug’s anchoring potential, in order to obtain results that justify the MOF to be chosen as a candidate for application as a drug carrier. This analysis resulted in obtaining a viable anchorage between the MOF lamellae. A simulation of the effects of temperature variation on the structure of the MOF EuBTC ([Eu2(MELL)(H2O)6]) and its effect on the luminescent properties was performed to obtain data that could validate your application with gunshot residues marker, aiming at its use in public safety. This analysis explored the potential of structural description of Sparkle/PM3 as well as the obtaining of luminescent properties, which led to the conclusion that the increase in temperature resulted in an increase in the emission quantum yield caused by the loss of water molecules contained in the first sphere of the coordinating polyhedron. For the application of MOFs in energy, an investigation was carried out regarding the degree of adsorption of the hydrogen gas and methane in the IRMOF-8 and in this one after the doping of its aromatic rings with aluminum atoms, in order to elucidate the effect that the realization of this Doping brings the storage capacity of these gases, for use in gas storage cylinders used in motor vehicles. And it was verified a slight reduction in the storage capacity of the methane gas, since for the hydrogen gas no significant changes were verified. Finally, a study was carried out to evaluate the capture capacity of carbon dioxide and hydrogen sulfide gases in IRMOF-8 and in this doped with aluminum, so the same structure of the previous study was used. It was found that doping gave a considerable increase in the degree of adsorption, being more effective for the carbon dioxide, whose interactions had energy of magnitude of a chemical adsorption.